2021
DOI: 10.1111/phpp.12715
|View full text |Cite
|
Sign up to set email alerts
|

The review of the light parameters and mechanisms of Photobiomodulation on melanoma cells

Abstract: Photobiomodulation (PBM) uses low‐intensity visible or near‐infrared light to produce beneficial effects on cells or tissues, such as brain therapy, wound healing. Still there is no consistent recommendation on the parameters (dose, light mode, wavelength, irradiance) and protocols (repetition, treatment duration) for its clinical application. Herein, we summarize the current PBM parameters for the treatment of melanoma, and we also discuss the potential photoreceptors and downstream signaling mechanisms in th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
8
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

2
5

Authors

Journals

citations
Cited by 22 publications
(8 citation statements)
references
References 92 publications
0
8
0
Order By: Relevance
“…The parameters of PBM that influence PBM’s effectiveness on the target cells and tissues include the light source, wavelength, power output, energy density, duration of irradiation, number of treatments, and the mode of light delivery (continuous or pulsed). For example, different wavelengths of light have different degrees of absorption, scattering coefficient, and reflection in the human body [ 72 , 73 ]. Near-infrared wavelengths have lower scattering factors and much higher penetration into tissues [ 74 , 75 ].…”
Section: Pbm Overviewmentioning
confidence: 99%
“…The parameters of PBM that influence PBM’s effectiveness on the target cells and tissues include the light source, wavelength, power output, energy density, duration of irradiation, number of treatments, and the mode of light delivery (continuous or pulsed). For example, different wavelengths of light have different degrees of absorption, scattering coefficient, and reflection in the human body [ 72 , 73 ]. Near-infrared wavelengths have lower scattering factors and much higher penetration into tissues [ 74 , 75 ].…”
Section: Pbm Overviewmentioning
confidence: 99%
“…Oh et al (2015) observed that blue light can further induce cell apoptosis and inhibit the proliferation of melanoma B16-F10 cells by activating the mitochondria (10). Chen et al (2022) summarized the effect of different light parameters on the growth of melanoma and its molecular mechanism; they believed that the inhibitory effect of PBMT is related to the influence of OPN photoacceptors and the activation of mitochondria and some signaling pathways (11). A similar result was evaluated by Shakibaiea et al (2020), using breast cancer cells (MCF-7) with inhibition of cell proliferation and metabolic activation by 435-nm LED irradiation (91).…”
Section: Photobiomodulation Therapy Of Osteosarcomamentioning
confidence: 99%
“…At present, PBM has been widely used to reduce inflammation, relieve pain, and promote wound healing ( 48 ). Meanwhile, PBM is also applicated in tumor treatment such as melanoma due to its non-invasive advantages, also named PBMT ( 10 , 11 ). Accordingly, research of the novel therapies such as PDT, PTT, and PBMT for tumor treatment is extremely important.…”
Section: Phototherapy Of Osteosarcomamentioning
confidence: 99%
See 2 more Smart Citations